Analysis of temporal bone thickness outside of the petrous temporal bone between superior semicircular canal dehiscence and normal patients. (February 2021) - Miao, Tyler; Johanis, Michael; Kaur, Taranjit; Duong, Courtney; De Jong, Russell; Willis, Shelby; Hong, Michelle; Romiyo, Prasanth; Hwang, Leslie; McArthur, David; Yang, Isaac; Gopen, Quinton
Highlights: SSCD is an uncommon neurotologic disorder. Root cause of SSCD may be localized to the petrous temporal bone. SSCD is less likely to be associated with global temporal bone degradation. Abstract: Background: SSCD is a rare inner ear disorder. This study aims to compare the thickness of the temporal bone beyond the petrous portion between healthy subjects and those with SSCD to determine whether the etiopathology of SSCD is localized to the petrous temporal bone or generalized to other parts of the temporal bone. Methods: A retrospective chart review of electronic medical records from September 2011 to February 2018 was conducted at a single-institution study at the University of California, Los Angeles. Participants were divided into two groups: Group 1 had a confirmed diagnosis of SSCD, while Group 2 had no known ear or temporal bone pathology. Participants' high-resolution coronal and axial temporal bone computed tomography scans were analyzed. Regions within the temporal bone were measured and compared between the two groups. Results: A total of 262 scans were included. Group 1 consisted of 103 scans, while Group 2 consisted of 159 scans. There was no statistically significant difference in the thickness of temporal bones between patients diagnosed with SSCD and patients without otologic disease. Conclusion: The results suggest that the etiology of SSCD is limited to the petrous portion of the temporal bone. SSCD may be unrelated to a larger process of global temporal bone degeneration. Additional clinical screening for regions outside the petrous temporal bone is not warranted unless SSCD patients present with symptoms characteristic of other temporal bone pathologies.